Effect of glycerol on pellet mill production efficiency - C N Groesbeck; Leland J McKinney; Michael D Tokach; Jim L Nelssen; Keith C Behnke; Joel M DeRouchey; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2007)
Crude glycerol is a by-product of the biofuels industry, which has the potential to be used as a feed ingredient in animal diets. However, little is known about glycerol's nutritional value or how it impacts feed quality and feed processing efficiency. Three experiments were conducted to evaluate the effects of glycerol on production efficiency of a pellet mill. In all three experiments, diets were manufactured, pelleted, and data collected at the KSU Grain Science Feed Mill. All diets were steam conditioned to 85Â°F and pelleted at 150Â°F using a CPM pellet mill equipped with a 4 mm × 32 mm pellet die. In Exp. 1, the six treatments were a corn-soybean meal-based swine grower diet formulated to contain 0, 3, 6, 9, 12, and 15% crude glycerol. Experiment 2 included seven treatments: the control with no added soy oil or glycerol, the control diet with 3 or 6% added soy oil, the control diet with 3 or 6% added glycerol, and the control with 6 or 12% of a 50:50 soy oil to glycerol blend. Experiment 3 included five treatments: a control with no added lactose or glycerol, the control diet with 3.6 or 7.2% lactose, or the control with 3.6 or 7.2% glycerol. Each experimental diet was replicated by manufacturing a new batch of feed three times. Glycerol lowered delta temperature, amperage, and motor load in Exp. 1, 2, and 3. The addition of glycerol consistently improved pellet quality. Production rate was not affected by the addition of glycerol; however, glycerol decreased total energy usage (KWh/t). Furthermore, glycerol can be added to a diet in combination with soy oil in a blend to improve production efficiency and pellet quality compared to a diet containing only soy oil. The addition of glycerol will improve the production efficiency of pelleting, pellet quality, and decrease energy cost when included in diets prior to pelleting.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Swine; Feed manufacturing; Glycerol; Pelleting